Solution-phase automated synthesis of an α-amino aldehyde as a versatile intermediate - Masui, Hisashi; Yosugi, Sae; Fuse, Shinichiro; Takahashi, Takashi (Beilstein Journal of Organic Chemistry, 2017)
A solution-phase automated synthesis of the versatile synthetic intermediate, Garner’s aldehyde, was demonstrated. tert-Butoxycarbonyl (Boc) protection, acetal formation, and reduction of the ester to the corresponding aldehyde were performed utilizing our originally developed automated synthesizer, ChemKonzert. The developed procedure was also useful for the synthesis of Garner’s aldehyde analogues possessing fluorenylmethyloxycarbonyl (Fmoc) or benzyloxycarbonyl (Cbz) protection.
Keywords: acetal formation; amino acid; automated synthesis; Garner’s aldehyde; reduction

Laboratory Automation in the Chemical Industries - Cork, D. G.; Sugawara, T. (Marcel Dekker Inc., 2002)

(untitled) - Li, J.; Ballmer, S. G.; Gillis, E. P.; Fujii, S.; Schmidt, M. J.; Palazzolo, A. M. E.; Lehmann, J. W.; Morehouse, G. F.; Burke, M. D. (Science, 2015)

(untitled) - Adamo, A.; Beingessner, R. L.; Behnam, M.; Chen, J.; Jamison, T. F.; Jensen, K. F.; Monbaliu, J.-C. M.; Myerson, A. S.; Revalor, E. M.; Snead, D. R.; Stelzer, T.; Weeranoppanant, N.; et al. (Science, 2016)

(untitled) - Seeberger, P. H.; Werz, D. B. (Nat. Rev. Drug Discovery, 2005)

(untitled) - Doi, T.; Fuse, S.; Miyamoto, S.; Nakai, K.; Sasuga, D.; Takahashi, T. (Chem. – Asian J., 2006)

(untitled) - Fuse, S.; Ikebe, A.; Oosumi, K.; Karasawa, T.; Matsumura, K.; Izumikawa, M.; Johmoto, K.; Uekusa, H.; Shin-ya, K.; Doi, T.; Takahashi, T. (Chem. – Eur. J., 2015)

(untitled) - Fuse, S.; Okada, K.; Iijima, Y.; Munakata, A.; Machida, K.; Takahashi, T.; Takagi, M.; Shin-ya, K.; Doi, T. (Org. Biomol. Chem., 2011)

(untitled) - Tanaka, Y.; Fuse, S.; Tanaka, H.; Doi, T.; Takahashi, T. (Org. Process Res. Dev., 2009)

(untitled) - Machida, K.; Hirose, Y.; Fuse, S.; Sugawara, T.; Takahashi, T. (Chem. Pharm. Bull., 2010)

(untitled) - Kher, S. S.; Penzo, M.; Fulle, S.; Finn, P. W.; Blackman, M. J.; Jirgensons, A. (Bioorg. Med. Chem. Lett., 2014)

(untitled) - Segade, Y.; Montaos, M. A.; Rodríguez, J.; Jiménez, C. (Org. Lett., 2014)

(untitled) - Vasudevan, N.; Kashinath, K.; Reddy, D. S. (Org. Lett., 2014)

(untitled) - Singh, P.; Manna, S. K.; Panda, G. (Tetrahedron, 2014)

(untitled) - Takahata, H.; Banba, Y.; Ouchi, H.; Nemoto, H. (Org. Lett., 2003)

(untitled) - Sa-ei, K.; Montgomery, J. (Tetrahedron, 2009)

(untitled) - Bhabak, K. P.; Proksch, D.; Redmer, S.; Arenz, C. (Bioorg. Med. Chem., 2012)

(untitled) - Sudhakar, N.; Kumar, A. R.; Prabhakar, A.; Jagadeesh, B.; Rao, B. V. (Tetrahedron Lett., 2005)

(untitled) - Chen, J.; Chen, X.; Bois-Choussy, M.; Zhu, J. (J. Am. Chem. Soc., 2006)

(untitled) - Passiniemi, M.; Koskinen, A. M. P. (Beilstein J. Org. Chem., 2013)

(untitled) - Karjalainen, O. K.; Koskinen, A. M. P. (Tetrahedron, 2014)

(untitled) - Upadhyay, P. K.; Kumar, P. (Synthesis, 2010)

(untitled) - Garner, P.; Park, J. M. (Org. Synth., 1992)

(untitled) - Foss, F. W., Jr; Snyder, A. H.; Davis, M. D.; Rouse, M.; Okusa, M. D.; Lynch, K. R.; Macdonald, T. L. (Bioorg. Med. Chem., 2007)

(untitled) - Ocejo, M.; Vicario, J. L.; Badía, D.; Carrillo, L.; Reyes, E. (Synlett, 2005)

(untitled) - Dondoni, A.; Perroni, D. (Org. Synth., 2000)

(untitled) - Jurczak, J.; Gryko, D.; Kobrzycka, E.; Gruza, H.; Prokopowicz, P. (Tetrahedron, 1998)

(untitled) - Roush, W. R.; Hunt, J. A. (J. Org. Chem., 1995)

(untitled) - Trajkovic, M.; Ferjancic, Z.; Saicic, R. N. (Tetrahedron: Asymmetry, 2012)

(untitled) - Hoffman, T. J.; Kolleth, A.; Rigby, J. H.; Arseniyadis, S.; Cossy, J. (Org. Lett., 2010)

(untitled) - Cortes-Clerget, M.; Gager, O.; Monteil, M.; Pirat, J.-L.; Migianu-Griffoni, E.; Deschamp, J.; Lecouvey, M. (Adv. Synth. Catal., 2016)

(untitled) - Clemens, A. J. L.; Burke, S. D. (J. Org. Chem., 2012)

(untitled) - Rush, J.; Bertozzi, C. R. (Org. Lett., 2006)

(untitled) - Jiang, S.; Li, P.; Lai, C. C.; Kelley, J. A.; Roller, P. P. (J. Org. Chem., 2006)

(untitled) - Martin, N. I.; Woodward, J. J.; Winter, M. B.; Marletta, M. A. (Bioorg. Med. Chem. Lett., 2009)

(untitled) - Lingamurthy, M.; Jagadeesh, Y.; Ramakrishna, K.; Rao, B. V. (J. Org. Chem., 2016)